Animal sculpture - Canizares, Susan (New York : Scholastic, 1999)
Presents different animal sculptures and their materials, including a rock fish, metal horse, and wooden pig.
Keywords: Sculpture -- Juvenile literature; Animal in art -- Juvenile literature